Penerapan Metode R&D dalam Pembuatan Aplikasi Pencarian Kos Berbasis Android - Agus Milani; Isdayani B.; Hasbi Hasbi (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This research aims to develop an Android-based boarding house search application that can provide boarding house information quickly, accurately, and easily accessed by the public, especially students and migrant workers. The research employed a Research and Development (R&D) method, encompassing user needs analysis, system design, application development, implementation, and system testing. The application is designed with key features such as searching for boarding houses based on location, price, facilities, and room availability, making it easier for users to make choices based on their needs. Furthermore, the application also provides features for boarding house owners to manage and promote their properties digitally. The application development process was conducted using the Android Studio platform with an integrated database to support real-time information management. System testing was conducted using the Black Box Testing method to ensure all application functions run according to user needs. The results show that the developed application can improve the efficiency of the boarding house search process, accelerate information access, and facilitate boarding house owners in promoting and managing property data. Therefore, this application is expected to be an effective digital solution to support mobile-based housing search services.